Muʿjam al-Mawrid li-al-Duktūr Rūḥī al-Baʿlabakkī (Dirāsah Waṣfiyyah Taḥlīliyyah) - Ahmad Hidayatullah Zarkasyi (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2015)
It is widely recognized that the compilation of dictionaries is closely related to people's awareness of their linguistic limitations, particularly in languages that are not their mother tongue. One of the major causes of these limitations is the inadequate mastery of vocabulary, accompanied by the perception among some individuals that language is of little importance in social life. In response to these challenges, dictionaries have become indispensable tools for overcoming limited language proficiency while simultaneously broadening users' cultural knowledge and intellectual horizons. As many linguists have emphasized, learning a language involves not only mastering its linguistic system but also understanding the culture and civilization associated with it. Among the most well-known dictionaries in the contemporary period is Al-Mawrid Dictionary by Dr. Rūḥī al-Baʿlabakkī, first published in 1996. The dictionary is organized according to the standard alphabetical order and follows the pronunciation-based school of lexicographical arrangement. It presents lexical entries with both Arabic and English meanings, making it a bilingual dictionary. Owing to its comprehensiveness and scholarly reputation, Al-Mawrid has been widely adopted in schools, Islamic boarding schools, and universities. Furthermore, it is regarded as one of the principal reference works for academic writing because of its extensive lexical coverage. For these reasons, the author considers an analysis of the methodology employed in this dictionary to be highly valuable and necessary.